Overmacht Dalam Tindak Pidana Pembunuhan Studi Komparatif Antara Hukum Pidana Islam dan Hukum Pidana Positif - Juwita, Nita; , Mutimatun Ni'ami, S.H., M.Hum; , Hartanto, S.H., M.H (2016)
The method used in the conduct of this study is the use of normative law research, which is intended as an attempt to bring the issues examined by the legal nature of the normative, the author uses descriptive analysis and comparative which describes how the basic law of coercion in the criminal act of murder under Islamic criminal law and according to the criminal law Positive, as well as how the implementation of criminal sanctions in terms of Islamic criminal law and the criminal law Positive. Coercion in the criminal act of murder under Islamic law can not remove the penalty, the scholars agreed that for anyone who has committed a murder on the grounds forced (Ikrah) then still getdiyat or ta'zir punishment. While coercion in the murder according to positive criminal law states that if the perpetrators of murder by reason of forced (coercion) the offender is obtained sentenced criminal, because of the positive criminal law coercion is one reason for removal of criminal.